Tau Phosphorylation and Aggregation as a Therapeutic Target in Tauopathies - Badiola, Nahuai; Suarez-Calvet, Marc; Lleo, Alberto (CNS & Neurological Disorders - Drug Targets, 2010)
Tauopathies are neurodegenerative diseases characterized by insoluble hyperphosphorylated deposits of the microtubuleassociated protein tau in the central nervous system. In these disorders, tau is believed to cause neurodegeneration and neuronal loss due to the loss of function of the normal protein, and/or the gain of toxic properties by generating multimeric species. The obstacles found in amyloid-based therapies in Alzheimer's disease, the most common tauopathy, have stimulated the search for alternative targets, including tau. In this article, we review the strategies aimed at reducing tau phosphorylation and aggregation as a target for drug intervention in tauopathies.
Keywords: immunization